Legal Study of the Role of Political Parties in Making Regional Regulations in the Regional People's Representative Council of Purbalingga Regency - Narendo, Virgiawan Moro; Rifqi Samhudi, Gamalel (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Countries that have democratic systems really need political parties as a forum for everyone to express their opinions, either as representatives of the people and also as a medium for peaceful political leadership. The role of political parties is a crucial element in determining the direction of a country's policies. In reality, there are often challenges such as the attraction of political interests, the fragmentation of party coalitions, and the influence of local political forces that play a role in influencing the final policy outcome. Therefore, it becomes interesting to understand how the role of political parties is related to the making of local regulations through their representatives in the DPRD. By using juridical normative research methods, it can be concluded that political parties play an important role in the concept of negotiations that occur during the process of making local regulations so that these regulations remain in accordance with the aspirations of the people and do not conflict with Pancasila.